Eldgjá and Laki: Two large Icelandic fissure eruptions and a historical-critical approach for interdisciplinary researchers working on past nature-induced disasters - Stephan F. Ebert; Katrin Kleemann (Volcanica)
The integration of archives of societies with archives of nature has led to collaborations between the natural sciences and the humanities. Not all those involved consider these archives equal, which led to some studies featuring explanations promoting nature as the prime agent in history. The field of the history of climate and society is currently experiencing a shift away from monocausal explanations. Cultural factors must be considered and their contribution to disasters must be examined. This paper introduces an easy-to-use step-by-step approach composed of crucial questions that need to be considered to analyze the entanglement of nature and society in relation to nature-induced disasters. The approach was developed by examining two large Icelandic fissure eruptions, Eldgjá (939–940 CE) and Laki (1783–1784 CE). The approach presented in this paper offers increased understanding across disciplinary cultures from the perspective of historians and is intended as a thought-provoking impulse for future studies.